Appropriate Technology For Post-Harvest Rice Processing - Gusti Hardiansyah (Jurnal Abdimas Madani dan Lestari (JAMALI), 2020)
Limited facilities and infrastructure in rice farming activities, especially in post-harvest processing has resulted in a farming communities become unproductive to processing their harvested products. Despite these problems has been tried to be overcome by the farming communities by making some tools for agricultural needs with tools and improvised materials, like a self-made rice thresher tools that made from used wood waste, of course the ability of productivity is very much different when using factory-made rice thresher. This PKM activity aims to introduce and train the farming communities to be able to process their rice crop yields using appropriate technology, like with a rice thresher machine and a rice husk machine. The main target in this PKM activity is a community of  Tani Jaya Mandiri Group which in Kelurahan Batu Layang RT05/RW13 Kecamatan Pontianak Utara, which still has limited facilities for their agricultural activities. The method applied in this PKM activity is the diffusion of science and technology, socialization and active participation from the community. So with the existence of this PKM activity, the farming community get knowledge and skills in processing their post-harvest rice products, and is expected to be able to help overcome their productiviy problems due to the limited agricultural facilities they have